Kisah inspiratif: Perjalanan meraih kebahagiaan dalam film The Pursuit of Happyness Karya Gabrielle Muccino - Khotimah, Siti (Maliki Interdisciplinary Journal, 2024)
This article examines the film “The Pursuit of happyness” as an audiovisual work that successfully combines elements of everyday life with philosophical principles. Based on a true story, this film depicts the life journey of Chris Gardner, a single father struggling with poverty and uncertainty, this study analyzes the theory of happiness from Jalaluddin Rahmat, Positive Psychology from Martin E.P Seligman, and the concept of happiness as a learning process from Wahyu Raharjo. Highlighting four key scenes, this article highlights messages of persistence, determination, and unyielding spirit. The article also provides deep insight into how film can be a source of inspiration and influence viewers’ perceptions and actions towards life.